Outcomes of psychoanalytic therapies - Rudolf, Gerd; Manz, Rolf (International forum of psychoanalysis, 1999)
Using a naturalistic design, 44 patients in psychoanalysis were examined with regard to qualitative and quantitative outcome of therapy. The results were compared with those from 56 dynamic and 164 inpatient therapies. Comparison of symptoms, diagnoses, and motivation prior to therapy led to the conclusion that the patient groups treated within these settings differed greatly. For this reason randomisation appeared to be an inadequate strategy for comparing groups in different therapeutic settings. Using different outcome criteria, it could be demonstrated that psychoanalysis patients on the whole attained good therapeutic results. The outcomes were the best in comparison with the other two therapy categories investigated. The use of different outcome criteria and observer perspectives (patient and therapist) led to therapy results with clear-cut differences. In the patient view, the main effect was cessation of psychosomatic, anxiety- and depression-related symptoms. The therapists furthermore reported clear-cut changes in the scales depicting relationship variables. The study presents success rates obtained on the basis of different outcome criteria and discusses them with special emphasis on the methodology of recording outcomes. The paper concludes by making recommendations for psychoanalysis studies yet to be planned.
Published online: 06 Nov 2010
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 23.03.2021